Listening to Bob Dylan - Starr, Larry (Music in American life., 2021)
"Listening to Bob Dylan seeks to reposition music and musical performance as central, essential aspects of Bob Dylan's art. Countering the tendency on the part of many scholars, journalists, fans, and casual listeners to regard Dylan primarily or even exclusively as a poet, or as a writer of lyrics, Starr presents Dylan's work as a complete package and a personal, unique synthesis of words, music, and performance. Starr aims to provide an unpretentious guide that will help readers enjoy Dylan's music and music performance to the fullest. By way of clarifying Starr's methodology, consider the question "How does it feel?" By itself it's an everyday, unremarkable expression: a salesperson hoping that the new shoes are fitting properly; a doctor or dentist assessing a patient's condition. Now imagine these same words being sung at you intensely by another person: "How does it feeeeel?" This is no longer that everyday question. Shaped by a familiar melody, rhythm, and vocal color, this can be one thing only, an evocation of Bob Dylan performing his iconic "Like a Rolling Stone." The words "How does it feel?" become "Like a Rolling Stone" only when Dylan's characteristic melody, rhythm, and vocal style are synthesized with them, becoming parts of an inseparable whole. The book is organized conceptually, in terms of what might be called listening focus: turning detailed attention first to Bob Dylan's varied vocal styles, then to his harmonica playing, then to the compositional elements of his songs, then to his choices of instrumentation, and so forth. This allows the reader to build a repertoire of listening experiences"--